Study on Character Input Methods Using Eye-gaze Input Interface - Murata, Atsuo; Hayashi, Kazuya; Moriwaka, Makoto; Hayami, Takehito (Human-Computer Interaction. Interaction Modalities and Techniques, 2013)
Four character input methods for eye-gaze input interface were compared from the viewpoints of input speed, input accuracy, and subjective rating on ease of input and fatigue. Four input methods included (1) I-QGSM (vertical), (2) I-QGSM (circle), (3) eye-fixation method, and (4) screen button. While the eye-fixation method (3) led to faster input, the I-QGSM (vertical) led to fewer errors. In conclusion, it is difficult to develop character input method that satisfies both speed and accuracy.